Region-specific nutrient intake patterns exhibit a geographical gradient within and between European countries. - Freisling, H; Fahey, M; Moskal, A; Ocké, M; Ferrari, P; Jenab, M; Norat, T; Naska, A; Welch, A; Navarro, C; Schulz, M; Wirfält, E; et al. (2010)
Until recently, the study of nutrient patterns was hampered at an international level by a lack of standardization of both dietary methods and nutrient databases. We aimed to describe the diversity of nutrient patterns in the European Prospective Investigation into Cancer and Nutrition (EPIC) study at population level as a starting point for future nutrient pattern analyses and their associations with chronic diseases in multi-center studies. In this cross-sectional study, 36,034 persons aged 35-74 y were administered a single, standardized 24-h dietary recall. Intake of 25 nutrients (excluding intake from dietary supplements) was estimated using a standardized nutrient database. We used a graphic presentation of mean nutrient intakes by region and sex relative to the overall EPIC means to contrast patterns within and between 10 European countries. In Mediterranean regions, including Greece, Italy, and the southern centers of Spain, the nutrient pattern was dominated by relatively high intakes of vitamin E and monounsaturated fatty acids (MUFA), whereas intakes of retinol and vitamin D were relatively low. In contrast, in Nordic countries, including Norway, Sweden, and Denmark, reported intake of these same nutrients resulted in almost the opposite pattern. Population groups in Germany, The Netherlands, and the UK shared a fatty acid pattern of relatively high intakes of PUFA and SFA and relatively low intakes of MUFA, in combination with a relatively high intake of sugar. We confirmed large variability in nutrient intakes across the EPIC study populations and identified 3 main region-specific patterns with a geographical gradient within and between European countries.